Materials for the creative biography of Tatyana Gippius (Based on the artist’s “diaries” for 1906–1908). Part I - Margarita Pavlova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article is dedicated to the creative biography of the Russian artist Tatyana Nikolaevna Gippius (1877–1957). The author bases on previously unknown materials from the Amherst archive (Massachusetts, USA) — T.N. Gippius’s letters- “diaries” of 1906–1908, addressed to her sister Zinaida Gippius, D.S. Merezhkovsky and D.V. Filosofov. The relevance of the study is determined by the increased interest to the artist’s works; in recent years, experts have turned to the study of various aspects of her creative heritage, which is for the most part lost: painted and graphic portraits of her contemporaries, book illustrations, icon-portraiture, and art albums. The “diaries”, the main content of which is dependant upon the chronicle of the Merezhkovskys’ neoChristian commune’s inner life (its younger “nest”, led by T.N. Gippius), at the same time contain a lot of additional information about the artist’s earliest, most fruitful period: years of study at the Higher Art School of the Imperial Academy of Arts, relations with the head of the workshop I.E. Repin, reporting exhibitions, the circle of the author’s interests, classes in book graphics and illustrations of children's books. A special place in the article is given to T.N. Gippius’ collaboration with the children’s magazine “Tropinka” (“Path”, 1906–1912), led by N.I. Manaseina and P.S. Solovyova. The Appendix provides a bibliography of T.N. Gippius’ book illustrations.